The Effect of Particle Size, Solid Content, NaCl and Na2CO3 on The Amilographic Characteristics of Corn Flour and Corn Starch - Tjahja Muhandri (Jurnal Teknologi dan Industri Pangan, 2007)
The ojective of this research was to investigate the effect of corn flour particle sizes (60, 80 and 100 mesh), solid content (40, 45, 50 and 55 gr sample), NaCl (1, 2, 3, and 4% w/w) and Na2CO3 (0.1, 0.3, 0.6, 0.9 and 1.2%, w/w) on the amilography properties of the corn flour and corn starch revealed. Which were characterised by using Brabender Amilograph. The study that initial temperature of gelatization, maximum temperature of gelatinization and maximum viscosity increased with the increased of particle sizess. In most cases, each increment of 1 gram solid content could increase maximum viscosity about 57 BU and 49 BU for corn flour and corn starch, respectivevely . More over, addition of Na2CO3 and NaCl upon corn flour could increase the initial temperature of geletinization, maximum temperature of geletinization, maximum viscosity and cold viscosity. In the case of corn starch, addition of Na2CO3 had no significant effect on initial temperature of gelatinization. Whereas this treatment could decrease the maximum temperature of gelatinization and increase maximum viscosity at low concentrations (